2017
DOI: 10.1155/2017/1514294
|View full text |Cite
|
Sign up to set email alerts
|

SIAE Rare Variants in Juvenile Idiopathic Arthritis and Primary Antibody Deficiencies

Abstract: Sialic acid acetylesterase (SIAE) deficiency was suggested to lower the levels of ligands for sialic acid-binding immunoglobulin-like receptors, decreasing the threshold for B-cell activation. In humans, studies of rare heterozygous loss-of-function mutations in SIAE gene in common autoimmune diseases, including juvenile idiopathic arthritis (JIA), yielded inconsistent results. Considering the distinct pathogenesis of the two main subtypes of JIA, autoinflammatory systemic (sJIA) and autoimmune oligo/polyartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…SIAE is an enzyme which catalyzes the removal of 9-O-acetylation modifications from sialic acids. Previous studies have demonstrated that some mutations in this gene are associated with susceptibility to common autoimmune disease, such as juvenile idiopathic arthritis [28]. However, Zhang et al [29] found no association between SIAE gene mutation and RA in a Han Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…SIAE is an enzyme which catalyzes the removal of 9-O-acetylation modifications from sialic acids. Previous studies have demonstrated that some mutations in this gene are associated with susceptibility to common autoimmune disease, such as juvenile idiopathic arthritis [28]. However, Zhang et al [29] found no association between SIAE gene mutation and RA in a Han Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…This notion was initially supported by studies with Siae knock-out mice that showed enhanced O-acetylation of α2-6-linked Sias on N-glycans and defective B cell tolerance formation (138). However, recently it was discovered that the B cell phenotype in the mice was related to unintended disruption of Dock2, but not Siae (139), and results from genetic association studies investigating the link between SIAE polymorphisms and autoimmunity are conflicting (140)(141)(142)(143). While it is generally accepted that O-acetylation masks sialoglycan ligands for Siglec-2, Siglec2 knock-out alone in mice was not sufficient to induce B cell abnormalities, but required additional knock-out of Siglecg, probably due to redundant functions of these Siglecs (144).…”
Section: Immune Regulation and Autoimmunitymentioning
confidence: 99%